Pengaruh Penggunaan Media Pembelajaran Quizizz pada Mata Pelajaran Informatika Terhadap Kemampuan Berpikir Kritis Siswa di SMP Negeri 5 Kuningan - Nabilah, Adelia Yuke; Haerudin, Haerudin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of using the Quizizz learning media on students' critical thinking skills in the subject of Informatics at SMP Negeri 5 Kuningan. This research uses a quantitative method with a quasi-experimental design involving two groups, namely the experimental group that is treated using the Quizizz media and the control group that uses the lecture method. Data will be collected through pretests and posttests to measure the improvement in students' critical thinking skills. The data collection technique in this research is using a questionnaire to determine the effectiveness of the Quizizz media on students' critical thinking skills. The results of the study are expected to provide a positive contribution to the development of more interactive and effective learning methods. Based on the hypothesis test, the average value of the results of students' critical thinking skills in the experimental class was 78.70, while the control group was 60.83. The results of the t-test showed a significance value (2-tailed) of 0.000 <0.05, it can be concluded that there is an influence of the use of Quizizz learning media on students' critical thinking skills and is included in the good category. The results of the distribution of student response questionnaires to see the influence of the use of Quizizz learning media on students' critical thinking skills with the results of the analysis stated that the overall average percentage was 81% and was included in the good category.